2010
DOI: 10.3168/jds.2010-3487
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a processing model for the Irish dairy industry

Abstract: A processing-sector model was developed that simulates (i) milk collection, (ii) standardization, and (iii) product manufacture. The model estimates the product yield, net milk value, and component values of milk based on milk quantity, composition, product portfolio, and product values. Product specifications of cheese, butter, skim and whole milk powders, liquid milk, and casein are met through milk separation followed by reconstitution in appropriate proportions. Excess cream or skim milk are used in other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(101 citation statements)
references
References 22 publications
(35 reference statements)
3
97
1
Order By: Relevance
“…It has been widely demonstrated that milk with desirable clotting characteristics, namely relatively short clotting time, good firming rate and high curd firmness at cut, results in higher cheese yield than poorly coagulating milk (Johnson et al, 2001;Pretto et al, 2013) and increased profitability for the dairy industry (Bynum and Olson, 1982;Formaggioni et al, 2005). The improvement of MCP is strongly advisable to enhance dairy sector efficiency, especially in countries were milk is predominantly destined to cheese production (Geary et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely demonstrated that milk with desirable clotting characteristics, namely relatively short clotting time, good firming rate and high curd firmness at cut, results in higher cheese yield than poorly coagulating milk (Johnson et al, 2001;Pretto et al, 2013) and increased profitability for the dairy industry (Bynum and Olson, 1982;Formaggioni et al, 2005). The improvement of MCP is strongly advisable to enhance dairy sector efficiency, especially in countries were milk is predominantly destined to cheese production (Geary et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Every month, Conseleite (the Brazilian Joint Council of Producers and Milk Processors) calculates the reference price for standard raw milk depending on the mix of dairy products, yield of industrial products, production costs and raw milk quality (Canziani and Guimarães, 2003). It is more advantageous for the dairy to remunerate the raw milk supplier for a raw material that improves production efficiency and yield (Geary et al, 2010b). However, there is no Brazilian program for pricing a kg of solid milk components, as proposed in this study.…”
Section: Raw Milk Prices and Ebtidamentioning
confidence: 97%
“…In dairies, whose production processes a wide variety of products that may generate intermediate products, such as cream and whey, which are raw materials for other products, optimization techniques have already been efficiently deployed (Banaszewska et al, 2013;Geary et al, 2010a;Geary et al, 2010b;Geary et al, 2012;Guan and Philpott, 2011;Milad and Faezeh, 2012). This optimization relies heavily on the production process, together with marketing and management of raw materials -raw milk which is considered a constraint, because of its irregular availability throughout the year given the seasonality of its production (Banaszewska et al, 2013;Brockington et al, 1992;Geary et al, 2012;Roma et al, 2009).…”
Section: Dairy Product Mixes and Total Contribution Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…The base milk price was included at 29.5 euro cents (c)/L with the A + B − C multiple component pricing system used for milk payment (Geary et al, 2010). A flat-rate value added tax payment was included on milk sales at 5.2% based on current national policy.…”
Section: Scenariosmentioning
confidence: 99%